The effect of politically homogenous neighbourhoods on affective polarization: evidence from Britain - Tilley, J; Hobolt, S (Wiley, 2024)
Affective polarization is increasingly evident around the world. This has been attributed in part to residential segregation by partisanship. The ‘Big Sort’ has meant that neighbourhoods in the US, and elsewhere, have become more homogenous in terms of vote. Yet, there is little systematic evidence on the relationship between homogenous partisan neighbourhoods and affective polarization. Does living near fellow partisans make people more negative towards the other side? In this Research Note, we use unique data from Britain to show that while people accurately recognize that their local area is more or less politically homogenous, neighbourhood political homogeneity is not correlated with any measure of affective polarization. These findings are robust to the type of political divide (partisanship or Brexit), the level of geography, length of residence and controls for ideology and social characteristics. We therefore suggest that while geographical sorting is an important phenomenon, it is unlikely to be a major cause of affective polarization.